Evaluation of Economic Interventions in Economic Blocks during an Economic and Sanitary Crisis - Carmin Montante; Clemente Hernandez-Rodriguez (Engineering Proceedings)
The purpose of this study is to evaluate the economic interventions that took place during the initial stages of the pandemic in 2020 in the US, Mexico, and Canada. These countries share a free trade agreement that indicates their willingness to cooperate in economic terms with each other and that they should adopt similar economic policies due to both their shared agreements and proximity. However, the economic interventions adopted by two of the three countries were not considered by the other, which makes for an interesting comparison. Interrupted time series analysis is a quasi-quantitative method that has recently been used in evaluating policy during a specific time. This study is interested in focusing on the economic interventions that were put into practice in neighboring countries that have formed a free trade alliance named USMCA. The method of a systematic analysis of interrupted time series will be used as a basis for organizing the article to provide further validity to the study.